The Effect of Sales Promotion (Through Facebook Media) on Interest in Buying Housing PT. Ascarya Builds Persada in Bengkulu City - Thariq Alhadi Wahid; Melda Yunita (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of sales promotion (via Facebook media) on interest in buying housing at PT. Ascarya Bangun Persada Partially There is one independent variable (x) that will be discussed in this study, namely Sales Promotion which is the object of this research is the Consumer Housing PT. Ascarya Bangun Persada. In this study, there are several data analysis techniques used, including using instrument tests, analysis of respondents' responses, simple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of the simple linear regression test, the regression equation is obtained as follows: Y = 3.759 + 1.003 (X). Based on the simple linear regression equation above, it can be interpreted that: The constant value of 3.759 means that if the Sales Promotion variable (X) on Purchase Interest (Y) is equal to zero, then the Buying Interest variable remains 3.759. The coefficient of X (Sales Promotion) of 1.003 means that if the Sales Promotion increases by one unit, the purchase interest value will increase by 1.003. From the results of the tests that have been carried out, it can be concluded that the Sales Promotion variable (Through Facebook Media) has a positive and significant effect on Buying Interest in Housing PT. Ascarya Builds Persada of Bengkulu